Receptor-mediated drug delivery of bispecific therapeutic antibodies through the blood-brain barrier - Pardridge, William M. (Frontiers in Drug Delivery, 2023)
Therapeutic antibody drug development is a rapidly growing sector of the pharmaceutical industry. However, antibody drug development for the brain is a technical challenge, and therapeutic antibodies for the central nervous system account for ∼3% of all such agents. The principal obstacle to antibody drug development for brain or spinal cord is the lack of transport of large molecule biologics across the blood-brain barrier (BBB). Therapeutic antibodies can be made transportable through the blood-brain barrier by the re-engineering of the therapeutic antibody as a BBB-penetrating bispecific antibody (BSA). One arm of the BSA is the therapeutic antibody and the other arm of the BSA is a transporting antibody. The transporting antibody targets an exofacial epitope on a BBB receptor, and this enables receptor-mediated transcytosis (RMT) of the BSA across the BBB. Following BBB transport, the therapeutic antibody then engages the target receptor in brain. RMT systems at the BBB that are potential conduits to the brain include the insulin receptor (IR), the transferrin receptor (TfR), the insulin-like growth factor receptor (IGFR) and the leptin receptor. Therapeutic antibodies have been re-engineered as BSAs that target the insulin receptor, TfR, or IGFR RMT systems at the BBB for the treatment of Alzheimer’s disease and Parkinson’s disease.